Reading Fictional Narratives to Improve Social and Moral Cognition: The Influence of Narrative Perspective, Transportation, and Identification - Wimmer, Lena; Friend, Stacie; Currie, Gregory; Ferguson, Heather J. (Frontiers in Communication, 2021)
There is a long tradition in philosophy and literary criticism of belief in the social and moral benefits of exposure to fiction, and recent empirical work has examined some of these claims. However, little of this research has addressed the textual features responsible for the hypothesized cognitive effects. We present two experiments examining whether readers’ social and moral cognition are influenced by the perspective from which a narrative is told (voice and focalization), and whether potential effects of perspective are mediated by transportation into the story or by identification with the protagonist. Both experiments employed a between-subjects design in which participants read a short story, either in the first-person voice using internal focalization, third-person voice using internal focalization, or third-person voice using external focalization. Social and moral cognition was assessed using a battery of tasks. Experiment 1 (N=258) failed to detect any effects of perspective or any mediating roles of transportation or identification. Implementing a more rigorous adaptation of the third-person story using external focalization, Experiment 2 (N=262) largely replicated this pattern. Taken together, the evidence reported here suggests that perspective does not have a significant impact on the extent to which narratives modulate social and moral cognition, either directly or indirectly via transportation and identification.